Effect of kangaroo mother care in terms of hospital stay among preterm infants in a tertiary health care center - E., Adarsh; D. B., Bindu Shri; G., Sahana (International Journal of Contemporary Pediatrics, 2020)
Background: Hypothermia, infections and ineffective breastfeeding are some of the commonest cause of deaths among premature and low birth weight infants. Kangaroo mother care is a well-known intervention to address the issues related to preterm births, such as hypothermia, infection and prolonged hospitalisation. Methods: This study was carried out in a tertiary care centre in Bengaluru on all preterm neonates of birth weight less than 2500 grams with stable hemodynamic conditions over a period of 18 months. Gestational age assessed by the new Ballard’s score, within 24 hours of life and anthropometry details of the neonate were recorded at 24 hours of life by the single observer. Kangaroo mother care was given for a minimum of one hour at a stretch per day and the effect on the preterm neonate in terms of hospital stay was assessed. Results: Kangaroo mother care has positive effects on the infants growth, neurodevelopmental outcome, reduction in the morbidities associated with preterm infants, and breastfeeding practices in mothers of preterm neonates. Conclusions: The study promotes awareness of KMC on preterm neonates considering all the benefits and positive effects of KMC on the infant as well as baby, and to the family and nation amongst the health care personnel as well as the society.